PERANCANGAN BUKU POP-UP RELIEF FABEL CANDI SOJIWAN SEBAGAI MEDIA BELAJAR MELUKIS ANAK USIA DINI - Muryasari, Desiana; Putra, Ambar Aditya; Yusuf, Andi Wahyu Zulkifli (Universitas Mercu Buana, 2023)
The current study used a research and development approach to create a pop-up book media. It was fable reliefs from the Sojiwan Temple. This media was intended as a pedagogical tool for children's painting education. The study involved 30 kindergarten students from Laboratori Pedagogia FIP UNY. The focal point of investigation was the fable relief found at the Sojiwan Temple. Data analysis used the Miles and Huberman model, encompassing data reduction, data presentation, and drawing conclusions. The qualitative data analysis were transformed into pop-up media using the Borg and Gall model. It included needs analysis, information gathering, planning, initial product design, design validation, design revision, limited trials, product refinement, extensive testing, final product revision, and production stages. Based on the characteristics of young children, this pop-up book was